Radiotherapy in Post-mastectomy Breast Cancer , Comparison of Treatment Outcome between Hypo-fractionated Radiotherapy und Conventional Radiotherapy . (Latakia University Journal -Medical Sciences Series, 2022)
The aim of this study was to compare Conventional fractionated radiotherapy (CFRT) and Hypo-fractionated radiotherapy (HFRT) in post-mastectomy breast cancer in terms of  loco regional control and toxicity.Data obtained from 360 breast cancer patients who received complete adjuvant radiotherapy treatment between January 2015 and December 2019 were retrospective analyzed . 160 patients received CFRT 2 Gy daily fractions at a total dose of 50 Gy (group 1), while 180 patients received HFRT 2.5 Gy daily for 15 fractions at a total dose of 40 Gy  (grup 2). All patients were treated on linear accelerator with 3‑dimensional conformal RT technique. Outcome was analyzed in terms of loco-regional control and toxicity. Median follow-up was 44.6  months . No difference was observed between two groups in terms of loco-regional recurrence and toxicities. The treatment outcomes of hypo-fractionated radiotherapy in the post-mastectomy breast cancer patients is comparable to the outcomes of conventional treatment at Tishreen Hospital as  reported from other studies, and HFRT can be implemented in resource-limited settings.